Odontogenic Keratocyst in an Edentulous Patient: Report of an Unusual Case - Alexandre Perez; Valentina Calcoen; Tommaso Lombardi (MDPI AG, 2023)
The purpose of this study was to report a rare case of an odontogenic keratocyst occurring in the edentulous jaw area. A 64-year-old man presented with a painful swelling of the right posterior mandibular vestibule that prevented him from wearing a complete lower denture. Upon intraoral clinical examination, the patient was totally edentulous and had two removable complete dentures. He had a fistula in the vestibular mucosa of edentulous site 48 that was painful upon palpation. Radiological examination revealed an unilocular radiolucent lesion with a continuous peripheral sclerotic border, centered on both the mandibular angle and right branch. Differential diagnosis mainly included a residual cyst and an odontogenic cystic tumor. The biopsy and the excisional material allowed a diagnosis of an odontogenic keratocyst to be made, the cyst being lined by a uniform parakeratinized squamous epithelium, corrugated in places, showing intercellular edema in places, with a well differentiated basal cell layer ranging from cuboidal to columnar in shape, a relatively thin, inflammation-free fibrous wall, and a cyst lumen that contained varying amounts of desquamated keratin. In this case, the surgical risk was represented by paresthesia of both the inferior alveolar and the lingual nerves. The lesion was enucleated without any complications, and the follow-up after 1 year did not reveal any nerve functional damage. Our case underlines the importance for the clinicians to consider a keratocyst in the differential diagnosis of cyst-like lesions presenting in an edentulous area.